Relationship between distinctive competence activities and export performance: a study of Rajasthan SMEs. (1st January 2013) - Roy, Ankur; Vyas, Vishal; Jain, Priyanka
This paper focuses on the various distinctive competence activities (DCA construct comprising of general administration, human resource, marketing, finance, and operations) of small and medium enterprises (SMEs) in Rajasthan state (India) and examines its relation with export performance (EP) of the firms. A sample of 397 was collected from SMEs in the state representing prominent seven industry sectors. A two-step structural equation modelling procedure is employed in this study for estimating parameters: a measurement model followed by a structural model. The results suggest that there is a strong relation between DCA and EP among the firms. Among the competence activities practiced by the firms, finance and marketing were the prominent ones. The entrepreneurs also showed good administrative skills and gave directions to the overall activities of the organisation. However, results suggested that the firms were weak in marketing and appropriate action needs to be taken by the entrepreneurs to strengthen this area.